TMT-based quantitative proteomics analysis of serum-derived exosomes in patients with juvenile gout - Ji, Zhuyi; Zheng, Shaoling; Liang, Ling; Huang, Lixin; Sun, Shanmiao; Huang, Zhixiang; He, Yuebing; Pan, Xia; Li, Tianwang; Huang, Yukai (Frontiers in Endocrinology, 2025)
ObjectivesThe purpose of this study was to compare the proteomics of serum-derived exosomes in juvenile gout (J-Gout), juvenile hyperuricemia (J-HUA) and oligoarticular juvenile idiopathic arthritis (oJIA).MethodsSerum-derived exosomes were isolated from patients using a qEV column combined with the ExoQuick-TC kit. The proteomics of serum-derived exosomes was analyzed by tandem mass tag (TMT)-labeled liquid chromatography-mass spectrometry (LC-MS/MS) technology. Proteins differentially expressed in J-Gout and the other two groups were identified. This was followed by volcano plot, hierarchical cluster, Venn diagram, gene ontology (GO), and Kyoto Encyclopedia of Genes and Genome (KEGG) pathway analyses.ResultsA total of 838 credible proteins were identified in serum-derived exosomes from the three groups. Eighty-eight differentially expressed proteins (13 upregulated and 75 downregulated) were identified in J-Gout when compared with J-HUA. One hundred twenty-one differentially expressed proteins (20 upregulated and 101 downregulated) were identified in J-Gout when compared with oJIA. A total of 166 differentially expressed proteins were identified in J-Gout, compared with J-HUA and oJIA respectively. Bioinformatic analysis indicated that the 166 differentially expressed proteins were significantly involved in “immune response”, “Fc epsilon RI signaling pathway” and “B cell receptor signaling pathway”. A total of 43 differentially expressed proteins were identified in J-Gout, compared with J-HUA and oJIA simultaneously. Six proteins were found highly expressed in J-Gout uniquely. ELISA results showed that dipeptidyl peptidase 4 (DPP4) and heparin cofactor 2 (SERPIND1) were the highest in J-Gout, which was consistent with the proteomic results. Correlation analysis revealed that exosome-derived DPP4 and SERPIND1 were positively correlated with C-reactive protein (CRP) and erythrocyte sedimentation rate (ESR).ConclusionThe protein composition of serum-derived exosomes in J-Gout was significantly differed from that in J-HUA and oJIA. DPP4 and SERPIND1 were uniquely highly expressed in J-Gout. Some possible mechanisms regarding the inflammatory response and coagulation complement system were proposed, which may provide helpful diagnostic and therapeutic insights for J-Gout.